(untitled) (Educação e Pesquisa, 2019)
The aim of this interview is to present the work and thoughts of Professor Françoise Lantheaume, who has been since 2012 the director of the Laboratory on Education, Culture, and Politics (ECP) at the University Lumiére Lyon, France. Françoise Lantheaume has been creating closer ties with School of Education at USP as a result of her international research into discrimination, racism, and religion in schools. Such study, named “Religions, discriminations et racisme en milieu scolaire (ReDISCO)”, will be carried out until 2020. It relies on collaboration between a group of French and foreign laboratories. In Brazil, it includes the University of Sao Paulo, the Federal University of Pernambuco, the Federal University of Paraná, the Federal University of Amazonas, and the Pontifical Catholic University of Rio de Janeiro. The interviewee’s publications and her involvement in a set of academic conferences reveal her contributions and amplify the debate about burning contemporary issues, especially those occurring in the school communities. Specifically, the issue of religion in the school, laity and discrimination, as well as the teachers´ suffering and the malaise in the school environment have been the objects of study by the laboratory headed by Françoise Lantheaume. These are, therefore, topics that mobilize both national and international concerns, which the journal Educação e Pesquisa have traditionally been discussing.